Factors Affecting Death and Severe Injury in Child Motor Vehicle Passengers - Wataru Ishii (MDPI AG, 2021)
Saving children from motor vehicle collisions is a high priority because the injury rate among motor vehicle passengers has been increasing in Japan. This study aimed to examine the factors that influence death and serious injury in child motor vehicle passengers to establish effective preventive measures. To identify these factors, we performed a retrospective study using a nationwide medical database. The data of child motor vehicle passengers younger than 15 years (n = 1084) were obtained from the Japanese Trauma Data Bank, registered from 2004 to 2019. Physiological variables, outcomes, and injury severity were compared between fatal and non-fatal patients and between those with and without severe injuries. Multivariate logistic regression analysis was performed to determine factors affecting fatality and severe injury. The Glasgow Coma Scale score (odds ratio (OR): 1.964), body temperature (OR: 2.578), and the Abbreviated Injury Scale score of the head (OR: 0.287) were identified as independent predictors of a non-fatal outcome. Systolic blood pressure (OR: 1.012), the Glasgow Coma Scale score (OR: 0.705), and Focused Assessment with Sonography for Trauma positivity (OR: 3.236) were identified as independent predictors of having severe injury. Decreasing the severity of head injury is the highest priority for child motor vehicle passengers to prevent fatality and severe injury.